A Real Estate Agency's Level Analysis of the Climate-Performance Relationship - Dolan, Shimon; Tziner, Aharon; Roy, Denis (Relations industrielles / Industrial Relations, 1984)
The autors aim at ascertaining whether perceived organisational climate alone explains any significant portion of variance in work performance and to examine whether the concomitant entrance of selected sociodemographic variables yields any additional contribution in explaining performance.